TOC1–PIF4 interaction mediates the circadian gating of thermoresponsive growth in Arabidopsis - Jia-Ying Zhu (Nature Portfolio, 2016)
The PIF4 transcription factor mediates the response of Arabidopsis seedlings to elevated temperature. Here the authors show that PIF4 interacts with the circadian clock component TOC1 which acts to suppress the PIF4-mediated temperature response in the evening.